Genotyping complex structural variation at the malaria‐associated human glycophorin locus using a PCR‐based strategy. (8th September 2020) - Algady, Walid; Weyell, Eleanor; Mateja, Daria; Garcia, André; Courtin, David; Hollox, Edward J.
Abstract: Structural variation in the human genome can affect risk of disease. An example is a complex structural variant of the human glycophorin gene cluster, called DUP4, which is associated with a clinically significant level of protection against severe malaria. The human glycophorin gene cluster harbours at least 23 distinct structural variants, and accurate genotyping of this complex structural variation remains a challenge. Here, we use a polymerase chain reaction‐based strategy to genotype structural variation at the human glycophorin gene cluster, including the alleles responsible for the U– blood group. We validate our approach, based on a triplex paralogue ratio test, on publically available samples from the 1000 Genomes project. We then genotype 574 individuals from a longitudinal birth cohort (Tori‐Bossito cohort) using small amounts of DNA at low cost. Our approach readily identifies known deletions and duplications, and can potentially identify novel variants for further analysis. It will allow exploration of genetic variation at the glycophorin locus, and investigation of its relationship with malaria, in large sample sets at minimal cost, using standard molecular biology equipment.